A Study on the “Competency View” of Core Literacy Curriculum Based on Dewey’s Empiricist Philosophy - Yongsheng Wei (Research and Advances in Education, 2024)
In the context of education in the new era, the cultivation of students’ core competencies and the enhancement of their core abilities are of paramount importance. Core competencies are critical factors for personal success and societal well-being, while core abilities are key elements for career development and the realization of value. Based on the analysis of Dewey’s empiricist philosophy, the cultivation of core competencies and the enhancement of core abilities lies in transforming traditional curricula and teaching methods, reforming and innovating educational experiences, and facilitating the integration of knowledge with practical application.